Immunomodulatory oligonucleotides inhibit neutrophil migration by decreasing the surface expression of interleukin‐8 and leukotriene B4 receptors. Issue 2 (February 2015) - Admyre, Charlotte; Axelsson, Lars‐Göran; von Stein, Oliver; Zargari, Arezou
Summary Neutrophils play important roles in many inflammatory diseases. The migration of neutrophils to the inflammatory site is tightly regulated by specific chemokines, of which interleukin‐8 (IL‐8) and leukotriene B4 (LTB4) constitute key mediators by binding to the surface receptors CXCR1/2 and BLT1, respectively. Oligonucleotides (ODN) containing CpG motifs mediate potent immunomodulatory effects through binding to Toll‐like receptor 9. So far, knowledge on how ODN can affect neutrophil migration during inflammation is lacking. This study demonstrates that several novel CpG ODN significantly down‐regulate the surface expression of CXCR1/2 and BLT1. In addition, the ODN significantly blocked IL‐8‐induced and LTB4‐induced neutrophil migration in vitro, as well as leucocyte migration in vivo demonstrated in mice by intravital microscopy and in a model of airway inflammation. The down‐regulation of CXCR1 is rapid, occurring 15 min after ODN stimulation, and can be mediated through an endosomally independent mechanism. Inhibition of the IL‐8 and LTB4 pathways may provide new opportunities of therapeutic intervention using ODN to reduce neutrophil infiltration during inflammation.